The effect of the annealing on the poly(vinyl alcohol) obtained by freezing-thawing - Gonzalez, Jimena Soledad (2011)
In the present work poly(vinyl alcohol) (PVA) hydrogels were obtained by freezing/thawing technique. The effect of thermal treatment on its performance was studied by annealing the hydrogels at five different temperatures, all of them between the water evaporation and the polymer melting ones, for 1 h. The main characteristics of hydrogels (glass transition temperature, crystallinity degree, equilibrium swelling degree, bound water content, gel fraction, water vapour transmission rate and diffusion exponent) were determined and the effect of annealing temperature was analyzed. Two different solution concentrations (5 and 10 wt.% of PVA) were used to prepare the hydrogels. It was clearly demonstrated that the studied properties markedly changed as a function of annealing temperature: the maximum swelling degree, the thickness change and the bound water content decreased whereas the gel fraction increased when annealing temperature was raised. An exponential relationship between gel fraction and crystallinity degree was found and the characteristics of hydrogels were correlated with both parameters. © 2011 Elsevier B.V. All Reserved rights.